Identification the effective compounds of pumpkin seeds and its possibility of application in some food products - Abd. Razak, Hanisah Kamilah; Mohammed Abed, Hind; Hassan, Luma Khairy (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2024)
This study included the use of local pumpkin seeds of Iraqi origin, which were examined in the Seed Examination and Certification Department. It was found that they are from the plant family Cucurbitaceae Jass, and their exact scientific name is Cucuriba pepo L. This study aims to use the local Iraqi pumpkin seeds and study their effective compounds to apply these seeds to some foods. The pumpkin seeds were dried at room temperature after they were peeled, cleaned, and washed. The fiber and proximate analysis were conducted. After that, the aqueous and alcoholic extraction of the defatted and non-defatted pumpkin seeds was carried out to detect the active compounds such as tannins, glycosides, coumarins, flavonoids, resins, and saponins. For the phenols, only a positive test was given for the alcoholic extract of the defatted seeds as an indication of their presence in the oil. As for steroids and terpenes, the result is negative, and each of the extracts has a significance that is not found in the seeds. Then, the vitamins were detected in a few different proportions in pumpkin seeds, with vitamin D (26.21). As for phenols, their percentage is 14.90%, which is considered the highest result, and 13.07% for vanillin. Finally, the results of the sensory evaluation were done after cupcakes, cookies, and pudding products made from pumpkin seed flour were manufactured. The residents highly accepted those food products. Therefore, this current study aimed to find a healthy alternative to seeds to make valuable and nutritious foods. This study indicated that the manufacture of cupcakes, cookies, and pudding products from pumpkin seed flour could improve the sensory and quality properties.